The “Danger” of Consensus Messaging: Or, Why to Shift From Skeptic-First to Migration-First Approaches - Russill, Chris (Frontiers in Communication, 2018)
Consensus messaging is a climate change communication strategy emphasizing the fact of scientific consensus on anthropogenic global warming (AGW). Its proponents encourage scientists, journalists, and educators to transmit consensus messages in hopes of improving public climate literacy. Critics of this approach question its methodology for determining consensus and its effectiveness as a strategy for improving public understanding and policymaking. I review these debates to determine what is at stake in disagreements over consensus messaging and suggest that issues of climate change danger are addressed too narrowly when the expectations, style and categories of consensus messaging are dominant. I recommend that “migration-first” approaches displace the priority of “skeptic-first” approaches to climate change communication, and that scholars begin asking what is owed to those most affected by climate change danger.